Modeling energetics and critical metabolic power in tethered-swimming - Filho, D.; de Castro, E. A.; Massini, D. A.; de Almeida, T. F.; Macedo, A. G.; Espada, M. C. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
The environmental constrains in swimming preclude the application of devises for the analysis of oxygen uptake (V.O2) with no impairments upon swimming velocity, and therefore also affecting the exercise intensity and the confidence on the estimated parameters of the velocitytime limited model. Hence, this study aimed to approach power-time limited model in tetheredswimming, focusing: (i) the estimate of the energetics in different workloads (WL), (ii) determine critical power (CP) and anaerobic reserve (W'), and (iii) compare CP to gas exchange threshold (GET), and respiratory compensation point (RCP). Sixteen swimmers (17.6±3.years, 175.8±10.5 cm, and 68.5±10.6 kg) performed an incremental ramp-test (IRT), attached to a weight-bearing pulley-rope system, to the assessment of peak oxygen uptake (V.O2peak), correspondent WL (WLV.O2peak), GET and RCP. The V.O2 kinetics was analysed at 95, 100 e 105% WLV.O2peak, describing oxygen deficit (O2Def = A1 x tau), tolerance (tLim) and V.O2peak attainment. Total energy (ETotal) demand was estimated [=EAnaer + (alpha x (V.O2peak-VO2rest) x tau) - (alpha x A1 x tau) x (1-e^((-t)/tau))] for each transition, with EAnaer [=(alpha x A1 x tau) + (beta x delta La- x body weight)]. The CP and W' were assessed from linear adjustment [PTotal=CP + (W' x 1/tLim)]. The ANOVA compared CP vs. GET and RCP, and EAnaer vs. W'. During swimming at 95, 100 and 105% WLV.O2peak, the V.O2 response attained 97.2±5.2, 100.4±3.8 and 101.8±5.7 %V.O2peak, which during IRT corresponded to 50.2±6.2 ml min-1 kg-1. The values of GET and RCP corresponded to 67.4±7.4 and 87.4±3.4% V.O2peak. The responses of ETotal and tLim during the transitions at 95 (515.8±138.9 kJ and 591.2±171.9 s), 100 (362.6±89.2 kJ and 356.4±91.3 s) and 105% (237.1±80.6 kJ and 231.2±63.5 s) were adjusted to estimate CP (0.84±0.22 kW) and W' (31.1±16.2 kJ). Considering the values of power at 100% (1.05±0.24 kW), the CP (79.8±10.1%) differed from GET and RCP (p<0.01), and W' values also differed from the average EAnaer (69.7±18.1 kJ, p<0.01) for the three transitions. The metabolic power corresponding to the CP was estimated in tethered-swimming with this physiological response characterizing the heavy to severe exercise boundary, which has been reported to range from 76 to 90% of V.O2peak. Despite the current value of CP is located at this range, it differed from RCP and therefore might not support the similar role in demarcating the heavy exercise domain. Moreover, Wf estimate seemed to underestimate the calculated EAnaer, which is otherwise aligned to the anaerobic stores estimated in supramaximal front-crawl performance to exhaustion.